MULTI-TARGETED ACTION OF A PLANT DERIVED FLAVONOID GLUCOSIDE 'APIGETRIN' AGAINST IMPORTANT MACROMOLECULAR TARGETS IN CANCER - AN IN SILICO VALIDATION - H. SHABEER ALI,; K. SREEJITH, (International Journal of Pharma and Bio Sciences, 2014)
Apigetrin, also known as Apigenin-7-O-Glucoside is a natural flavonoid glucoside. There are very few reports regarding its anticancer activity. From the present in silico study it was observed that Apigetrin can act as a multi-targeted agent that targets 6 different anticancer drug targets like MDM2, PI3 Kinase, Focal Adhesion Kinase, Topoisomerase-iiï¢, DHFR and P-glycoprotein that we have studied. Apigetrin showed more negative binding free energies as an indication of favorable interaction against these targets. With the help of online property explorer, the mutagenic activity and reproductive effects of Apigetrin was identified. In order to remove the predicted toxic effects without affecting its binding affinity and molecular properties, slight modifications were carried out and a new structure was designed without toxic properties. The molecular properties and binding affinities of the proposed structure towards the above mentioned targets was found to be enhanced when compared with Apigetrin and the standard inhibitors.